2006
DOI: 10.1152/physiolgenomics.00026.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional characterization of a superfamily of microbial inwardly rectifying potassium channels

Abstract: Cloning and functional characterization of a superfamily of microbial inwardly rectifying potassium channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…Each of the K ϩ transport systems Trk1, Trk2, GlnQHMP, and Kch was tested for its role in K ϩ uptake by complementing the E. coli strain TK2420 with these systems. E. coli TK2420 is a wellestablished model organism to characterize K ϩ transporters because of its lack of constitutive transporters and inability to transport K ϩ (31,(61)(62)(63). We observed that complementing E. coli TK2420 with Trk1, Trk2, or GlnQHMP facilitated significant K ϩ acquisition and enabled normal growth in low K ϩ concentrations and under stress conditions imposed by high salt concentrations and low pH.…”
Section: Discussionmentioning
confidence: 95%
“…Each of the K ϩ transport systems Trk1, Trk2, GlnQHMP, and Kch was tested for its role in K ϩ uptake by complementing the E. coli strain TK2420 with these systems. E. coli TK2420 is a wellestablished model organism to characterize K ϩ transporters because of its lack of constitutive transporters and inability to transport K ϩ (31,(61)(62)(63). We observed that complementing E. coli TK2420 with Trk1, Trk2, or GlnQHMP facilitated significant K ϩ acquisition and enabled normal growth in low K ϩ concentrations and under stress conditions imposed by high salt concentrations and low pH.…”
Section: Discussionmentioning
confidence: 95%
“…These strains cannot grow on a media with low (1-10 mM) potassium (28), but expression of potassium channels or transporters can restore their growth (29). This strategy was successful for isolation of potassium channels and transporters (30) as well as the mutations that activate potassium channels (31,32). A similar approach but utilizing the Saccharomyces cerevisiae K ϩ transport-deficient mutant was also used to study functional substitutions in the Kir2.1 inwardly rectifying potassium channel (33).…”
mentioning
confidence: 99%
“…Instead, the dominant lipids are phosphatidylethanolamines (PE), and phosphatidylglycerols (PG), 20 in which KirBac channels are active. 11,21 As eukaryotic organisms evolved, PIP 2 and other acidic lipids became increasingly concentrated in plasmalemmal membranes. The unwonted inhibitory effect of PIP 2 on KirBac1.1 activity is such that at the predicted PIP 2 concentrations in mammalian membranes (~1% of phospholipids), 22,23 KirBac-based channel activity would be completely suppressed.…”
mentioning
confidence: 99%